2017
DOI: 10.1111/gbb.12398
|View full text |Cite
|
Sign up to set email alerts
|

ASIC1A in neurons is critical for fear‐related behaviors

Abstract: Acid-sensing ion channels (ASICs) have been implicated in fear-, addiction-, and depression-related behaviors in mice. While these effects have been attributed to ASIC1A in neurons, it has been reported that ASICs may also function in non-neuronal cells. To determine if ASIC1A in neurons is indeed required, we generated neuron-specific knockout mice with floxed Asic1a alleles disrupted by Cre recombinase driven by the neuron-specific synapsin I promoter (SynAsic1a KO mice). We confirmed that Cre expression occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
39
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 37 publications
3
39
0
1
Order By: Relevance
“…whereas others have not observed vision-based abnormalities that would disrupt detection of visual cues in our experiments 28. For example, in fear conditioning, the CS was 20 seconds (auditory tone) or continuous (context), and the footshock (US) was only 1 second 4,19,20. The results here suggest that altering the timing of the CS-US relationship might influence the outcomes in those other paradigms.…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…whereas others have not observed vision-based abnormalities that would disrupt detection of visual cues in our experiments 28. For example, in fear conditioning, the CS was 20 seconds (auditory tone) or continuous (context), and the footshock (US) was only 1 second 4,19,20. The results here suggest that altering the timing of the CS-US relationship might influence the outcomes in those other paradigms.…”
mentioning
confidence: 80%
“…5,7,[13][14][15] Effects of ASIC1A disruption on dendritic spine density and glutamate receptor composition and function have been reported, 7,13,15,16 as well as effects on long-term potentiation 5,7,17 and long-term depression. 4,6,[17][18][19][20] These deficits were reproduced with amygdalaspecific ASIC1A disruption, 17 and a deficit in contextual fear memory was rescued by expressing ASIC1A in the amygdala. Consistent with the above observations, effects of ASIC1A on Pavlovian conditioning to aversive stimuli have been described.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…For example, acid-sensing ion channel 1a (ASIC1a) is recognized to contribute to the development of fear behaviors. 22,23,25 Therefore, the observed increases in the rats' serum ACTH and noradrenaline levels were expected. However, the significant increase in the ACTH concentration of male rats compared with females was surprising, given that previous work suggested that females generally demonstrate higher increases in response to stress.…”
Section: Discussionmentioning
confidence: 77%
“…This depression causes that they begin to produce addictive behaviors and force the consumer to look for contexts of easy access to this type of illegal drugs. 4 …”
Section: Introductionmentioning
confidence: 99%